# I Help with expression $F(it)-F(-it)$ in the Abel-Plana form

Tags:
1. Aug 7, 2017

### JasonPhysicist

I´m having a problem with the value of the expression

$F(it)-F(-it)$, found on the Abel-Plana formula, where $$F(z)=\sqrt{z^2 + A^2}$$, with $A$ being a positive real number (F(z) is analytic in the right half-plane).

Well, I know the result is $F(it)-F(-it)=2i\sqrt{t^2 -A^2}$, for $t>A$

Starting from the fact that the function has branch points $z=\pm iA$ I´d have to go around around these points to obtain the above result. However, to obtain it, I should have

$$F(-it)=-F(it)$$, which means $F(it)=i\sqrt{t^2 -A^2}$ and $F(-it)=-i\sqrt{t^2 -A^2}$.

I honestly can't see why that happens and I can't formulate a proof for it.

Any help would be appreciated.

2. Aug 11, 2017

### Someone2841

I think $F(it)-F(-it)=0$, no? This is unsurprising given that the only occurrence of z in the formula is squared, and $z^2$ is an even function. In any case:

$F(it)=\sqrt{(it)^2+A^2}=\sqrt{-t^2+A^2}$
and
$F(-it)=\sqrt{(-it)^2+A^2}=\sqrt{-t^2+A^2}$

Last edited: Aug 11, 2017